2018
DOI: 10.15537/smj.2018.9.22630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on coagulation screening tests and platelet counts in a Sudanese male adults population

Abstract: Objectives:To study the effects of heavy cigarette smoking on coagulation (CGG) screening tests and platelet counts (PLTs) in a Sudanese male adults population.Methods:A case control study was conducted at both Kosti and Gabalein towns, Sudan, during October 2016 to May 2017. A 100 adult cigarette smokers were selected and another 100 matched non-smokers were selected as healthy controls. Blood samples were collected in trisodium citrate anti-coagulant for prothrombin time (PT), partial thromboplastin time (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
(17 reference statements)
3
10
2
Order By: Relevance
“…According to our findings, the platelet count mean values and multiple linear regression showed a statistically significant decrease among Tombak users compared tonon-Tombak users. Similar results in previous studies were reported with significantly lower platelet counts in chewing tobacco users, Shisha smoking, and heavier chronic smokers than non-smokers [ 21 ]. A study conducted by Oaikhena et al [ 24 ] showed that the tobacco snuff could induce platelet count reduction among adult Wistar rats.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to our findings, the platelet count mean values and multiple linear regression showed a statistically significant decrease among Tombak users compared tonon-Tombak users. Similar results in previous studies were reported with significantly lower platelet counts in chewing tobacco users, Shisha smoking, and heavier chronic smokers than non-smokers [ 21 ]. A study conducted by Oaikhena et al [ 24 ] showed that the tobacco snuff could induce platelet count reduction among adult Wistar rats.…”
Section: Discussionsupporting
confidence: 91%
“…The study results indicated that the study population was entirely male. Oral Tombak SLT use in Sudan is a male-dominant habit, and females normally did not use Tombakor smoke cigarettes due to socio-cultural issues [ 7 , 21 ]. The age for the two groups varied from 20 to 65 years old, with a mean age of 39.46 ± 12.72 years old for the Tombak users group and 39.53 ± 12.21 years old for the non-Tombak users, and there was no statistically significant difference regarding age ( p -value 0.968).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, smoking may activate thrombopoietin which stimulates platelet production [20]. It had also been reported that smoking caused a hypercoagulable state of blood, which directly promoted thrombosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, positive linear correlation was found between the pack-years, reflecting the number of cigarettes smoked daily and the time of smoking, and NLR [ 53 , 55 ]. However, our study revealed the negative linear correlation with the number of cigarettes/day as well as duration of tobacco use and platelet and PLR values in GO group, which may be caused by nicotine-induced decreased thrombopoietic activity in smokers [ 56 ]. Smokers with GD who present higher values of WBC, neutrophil, eosinophil counts and NLR values can be easily identified during routine morphology check-up, and may benefit from preventive actions.…”
Section: Discussionmentioning
confidence: 99%